2020
DOI: 10.1093/jas/skaa376
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of regression and fat-free diet methods for estimating ileal and total tract endogenous losses and digestibility of fat and fatty acids in growing pigs

Abstract: An experiment was conducted to 1) compare the regression and fat-free diet methods for estimating total or basal endogenous losses of fat (ELF) and fatty acids (ELFA) and true digestibility (TD) or standardized digestibility (SD) of fat and fatty acids in growing pigs and 2) compare these estimated values at the end of the ileum and over the entire intestinal tract. Ten barrows (initial body weight: 45.1 ± 2.8 kg) were surgically fitted with a T-cannula in the distal ileum, and allotted to 1 of 5 experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 39 publications
2
7
1
Order By: Relevance
“…Basal ELF and ELFA at the end of the ileum and over the entire intestinal tract were similar to our previous results [ 11 ]. Even when experimental conditions, such as fat-free diet composition, sample collection, and analytical procedures, were strictly controlled, small differences in basal ELF and ELFA can be observed between the two experiments.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Basal ELF and ELFA at the end of the ileum and over the entire intestinal tract were similar to our previous results [ 11 ]. Even when experimental conditions, such as fat-free diet composition, sample collection, and analytical procedures, were strictly controlled, small differences in basal ELF and ELFA can be observed between the two experiments.…”
Section: Discussionsupporting
confidence: 91%
“…Our previous study showed that correcting apparent ileal digestibility (AID) for basal endogenous losses of fat (ELF) and fatty acids (ELFA) obtained by the fat-free diet method can accurately estimate SID values [ 11 ]. Therefore, the objective of the current study was to determine the AID and SID of fat and fatty acids in different oil sources for growing pigs and to develop prediction equations for SID of fat based on fatty acid composition.…”
Section: Introductionmentioning
confidence: 99%
“…Intestinal organoids can also be used to test the effects of nutrients on epithelial homeostasis. For instance, the treatment of piglet organoids with dietary vitamin A reduced buddings and markers for differentiated cells while it increased stem cell markers [ 45 ]. In another study, treatment of pig organoids with glutamate increased epithelial proliferation [ 46 ].…”
Section: Phenotype Of Livestock Intestinal Organoidsmentioning
confidence: 99%
“…High true digestibilities are commonly observed after correction by EEE ( Gutierrez et al, 2016 ). The classical approach of using EEE is to assign digestible values to dietary sources ( Chen et al, 2019 ; Wang et al, 2020b ). However, knowing EEE becomes even more critical when researchers seek to model digestion and absorption of energy and nutrients in pigs ( Birkett and de Lange, 2001 ; Strathe et al, 2008 ).…”
Section: Resultsmentioning
confidence: 99%
“…Regression analysis has been used to quantify EEE and to calculate true digestibility of both complete diets and ingredients ( Jørgensen et al, 1993 ; Su et al, 2015 ). However, the regression method has not been tested under conditions more reflective of commercial practice; for example, most previous research has utilized purified or semi-purified diets combined with restricted feed intake ( Wang et al, 2020b ). To achieve precision in diet formulation, it is essential to understand if the relatively low concentration of EE found in cereal grains is of lower digestibility than EE provided by a fat-rich ingredient.…”
Section: Introductionmentioning
confidence: 99%